2014
DOI: 10.1111/ped.12393
|View full text |Cite
|
Sign up to set email alerts
|

Increased satisfaction of maternity hospital staff involved in fetal telediagnosis

Abstract: Questionnaires were sent to 14 maternity hospital staff members for qualitative assessment at the start of fetal telediagnosis and at the end of the study using a five-point Likert scale: 5, I strongly think so; 4, I think so; 3, I can't decide; 2, I don't think so; 1, I never think so. Ten questionnaires were returned to us (71%). The results showed that the staff reported a significant increase in confidence in performing fetal cardiac screening (score 2.3 at start, 3.4 at study completion; P = 0.034), the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Health care professionals' satisfaction is as important as patient satisfaction in telemedicine delivery. Settings such as a maternity hospital, 25 a cardiology hospital, 26 intensive care units (ICUs), 27,28 and primary care practices 7,29 have found positive telemedicine satis-faction among health care professionals. However, several studies have reported either no significant changes in both perceived and real job satisfaction by delivering telemedicine services 30,31 or mixed results.…”
mentioning
confidence: 99%
“…Health care professionals' satisfaction is as important as patient satisfaction in telemedicine delivery. Settings such as a maternity hospital, 25 a cardiology hospital, 26 intensive care units (ICUs), 27,28 and primary care practices 7,29 have found positive telemedicine satis-faction among health care professionals. However, several studies have reported either no significant changes in both perceived and real job satisfaction by delivering telemedicine services 30,31 or mixed results.…”
mentioning
confidence: 99%
“…11,13,14 Telemedicine also has the potential to upskill DGH staff and has facilitated the education of clinicians in screening methods. 10,15 For example, Hishanti et al found increased skills in staff and improved screening. 15 Telemedicine enabled staff to consult with specialists on subtle anomalies, and this led to better identification of abnormalities and resulted in increased referrals.…”
Section: Introductionmentioning
confidence: 99%
“…10,15 For example, Hishanti et al found increased skills in staff and improved screening. 15 Telemedicine enabled staff to consult with specialists on subtle anomalies, and this led to better identification of abnormalities and resulted in increased referrals. 15 A 'Fetal Ultrasound Telemedicine' pilot, funded by the Academic Health Science Network North East and North Cumbria (AHSN NENC), commenced in October 2015.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations